2022
DOI: 10.3390/ijerph20010178
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Productivity Differences in Healthcare Systems: The Case of the European Union

Abstract: This study aims to identify significant differences between the countries of the European Union, follow the course of achievement of the convergence objectives, assess developments against specific common characteristics of the countries, and propose possible measures that could improve the state of health in the EU as a whole by implementing standard cohesion policies. To compare efficiency and productivity among the states of the European Union, we used data envelopment analysis (DEA) and the Malmquist produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…This is a crucial factor to consider in the healthcare industry because rising costs can restrict patient's access to vital care and burden the economic resources of healthcare organizations. Preventative care and early intervention can reduce costly treatments and boost economic efficiency [49]. This may include health education, screening, and lifestyle modification.…”
Section: Introductionmentioning
confidence: 99%
“…This is a crucial factor to consider in the healthcare industry because rising costs can restrict patient's access to vital care and burden the economic resources of healthcare organizations. Preventative care and early intervention can reduce costly treatments and boost economic efficiency [49]. This may include health education, screening, and lifestyle modification.…”
Section: Introductionmentioning
confidence: 99%
“…The second method is data envelopment analysis (DEA), which could provide a more accurate measure of efficiency by incorporating healthcare production functions. [26][27][28] This method can also be extended to use the slack based measure (SBM) model and the Malmquist model in combination with a panel regression model or for dynamic analysis. 29,30 In China, a cluster of healthcare resources can be found in developed provinces and cities, but the geographic accessibility of healthcare resources is poor in underdeveloped provinces and cities.…”
Section: Introductionmentioning
confidence: 99%
“…The second method is data envelopment analysis (DEA), which could provide a more accurate measure of efficiency by incorporating healthcare production functions. 26-28 This method can also be extended to use the slack based measure (SBM) model and the Malmquist model in combination with a panel regression model or for dynamic analysis. 29,30…”
Section: Introductionmentioning
confidence: 99%
“…For health systems efficiency, in 2001, based on the findings of the World Health Report 2000 Evans et al further estimated the relation between the health outputs (population health) and inputs, and revealed that besides increasing health resources input, most countries could achieve important gains by using the actual resources more efficiently 20. Following, many scholars explored the efficiency of the health systems in Asian countries,21 Organisation for Economic Cooperation and Development countries,22 23 European Union state,24 Eastern Mediterranean Region,25 Middle East and North Africa26 and ASEAN countries,27 etc, and the findings suggested that differences of the health systems efficiency existing among regions and countries and many of the countries still need to make efforts to improve the health systems efficiency. Besides the cross-national researches, there are also a number of studies examining the health systems efficiency from a single country’s perspective.…”
Section: Introductionmentioning
confidence: 99%